TANTANGAN DAN PELUANG SUMBER DAYA MANUSIA MENGHADAPI MASYARAKAT EKONOMI ASEAN - Wahyu Murti (Fakultas Ekonomi Universitas Borobudur, 2015)
Asean Economic Community will be established as an econimic region with a hihg level of competition that rewuires a policy include competition policy, consumer protection, Intellectual Property Rights (IPR), taxatin and E Commerce.Problems in order to welcome the Asean Economic Community in 2015 is whether the human resources in Indonesia is ready ?Indonesia faces challenges in the faceof the Asean Economic Community is not only from within the country but also ASEAN countries and countries outside ASEAN, among others, India, Korea and China. Challenges faced include the competitiveness of Indonesia’s labor.Indonesia has a great opportunity to be able to open and establish a broader market that ncourages employment opportunities in ASEAN. The largest population in ASEAN have the opportunity to send their employment with Human Resource skilled, creative, innovative and quality.